Ecological Succession in the Mangrove Ecosystem bibliographic/scientometric analysis (Research, Society and Development, 2022)
The research aimed to carry out a bibliographic review of publications indexed in the Web of Science (WoS) on ecological succession in Mangroves, highlighting the methods used in the studies. The time frame was from 1945, which is the beginning of the database, to June 2022. The following keywords were used: “ecological succession” and “forest mangrove”, not obtaining any result; “succession and mangrove”, resulted in 53 publications, which dealt specifically with succession in mangroves. From this an analysis of the scientific production on the subject were carried out; analysis of the methods used and the importance of ecological succession for the mangrove. As a result, 2021 had the highest number of publications and citations; the author Quen Chen was the most prominent, with five publications; the most relevant journal was Elsevier with 22 published studies; as for the country, China stood out with twelve publications, Brazil was the second with seven articles published. Among the analyzed methods, the Geography Information System – GIS was the most used (23 surveys), considered the most efficient and current method for monitoring areas in succession. In view of this, it is understood that the bibliographic study is essential to improve knowledge on the subject, it is also necessary to carry out more research on ecological succession to understand the vegetation dynamics and then seek a mechanism for conversation in mangrove areas.